Bridging Language Gaps in Rollingstock Engineering: An English for Specific Purposes (ESP) Perspective in Vocational Education - Rizka Maulina Wulandari; Eda Maaliah; Halim Ahmad Faizin; Muhyiddin Aziz; Dian Palupi (CV Wahana Publikasi, 2025)
As vocational education becomes increasingly connected to global industry demands, using English effectively is important for students preparing for professional careers. This study analyzes how English for Specific Purposes (ESP) learning can better support Rollingstock Engineering students to develop their communication skills and language knowledge. Using a descriptive qualitative approach, data were gathered through a structured questionnaire administered to 114 second-semester students at the State Polytechnic of Madiun. The questionnaire focused on students’ learning preferences, classroom experiences, perceptions of English learning, and expectations regarding English use in their future careers. The findings reveal that while students recognize English as essential for their professional development, current instruction remains too general and lacks authentic, industry-based content. Most students demonstrated strong career-oriented motivation and viewed English as an important tool for employability, technical communication, and workplace interaction. In addition, the data indicate that students prefer collaborative and experiential learning activities. Students also emphasized the importance of learning technical vocabulary, understanding engineering documents, and practicing communication relevant to maintenance, safety procedures, and industrial operations. These findings highlight the urgent need for a specialized ESP syllabus specifically designed for Rollingstock Engineering students. Developing teaching materials and textbooks that are combined with learning activities based on real workplace situations and authentic communication, is essential to reduce the gap between classroom instruction and the actual demands of the industry. The study suggests that aligning English instruction with real professional practices can better prepare vocational students to communicate effectively, confidently, and professionally in the global rollingstock engineering industry.